ANALISIS PENGARUH FAKTOR-FAKTOR MODAL MANUSIA TERHADAP PRODUKTIVITAS TENAGA KERJA INDUSTRI KENDANG JIMBE - Zulfa, Laila Zakiyatul; Pudjihardjo, M. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The election of this case is based on the fact that kendang jimbe has known as one of the superior products in Blitar city. Thus, this industry is expected to develop and build up the economy with the range of working opportunities offered and be able to improve labor productivity through human capital. This study aims to find out the influence of education level, working experience, and health condition on the level of labor productivity in the kendang jimbe industry. Meanwhile, the method of this study used a quantitative approach with a multiple linear regression model using Eviews 10. Moreover, the data used are primary data that is collected directly by spreading questionnaires. The population of this study is the laborers in the kendang jimbe industry located in Tanggung, Blitar city. They are an annount population. The sample used is about >30 laborers based on the job classification at kendang jimbe. After conducting the study, the result shows that the variable of education level, working experience, and health condition at each job classification has an influence or relation with the level of labor productivity. Health condition is the most dominant variable that influences labor productivity. In producing kendang jimbe, it requires high-quality human capital from each labor. The high-quality human capital of laborers in kendang jimbe will affect the achievement of the goal of the industry.